Chemopreventive Properties of Tolfenamic Acid: A Mechanistic Review - Feldman, David; Leahy, Elizabeth; Lee, Seong-Ho (Current Medicinal Chemistry, 2018)
Tolfenamic acid is one of the conventional non-steroidal anti-inflammatory drugs (NSAIDs) commonly used for the treatment of inflammation, migraines and pain. There has been a growing body of experimental evidence that tolfenamic acid possesses anti-cancer activity. However, in order to develop a therapeutic strategy using tolfenamic acid for the treatment of cancer, further research is required to highlight reliable cellular and molecular mechanisms of anti-cancer properties. Tolfenamic acid has been shown to alter the expression of several genes that represent cancer hallmarks including apoptosis, growth arrest, angiogenesis and metastasis. Recently, a couple of research groups including ours reported that tolfenamic acid targets multiple oncogenic or tumor suppressive signaling pathways in various types of cancer models. Here, we highlight multiple molecular targets responsible for the anti-cancer mechanism of tolfenamic acid and the benefits of combinational use of this drug with other anti-cancer drugs.
Keywords: apoptosis